Development of a single phase active power filter for rectifier load - Mat Yusoh, Mohd Abdul Talib (2013)
This project presents the employment of a single-phase active power filter (APF) to compensate harmonics generated by battery charger. The presence of the harmonics leads to various problems and poor power quality. The objectives of this project are to reduce the harmonic distortion of the single-phase system with battery charger load. The operation of APF is verified using the simulations in Matlab/Simulink. Conventional proportional-integral-derivative (PID) control based Shunt APF is being used to regulate the DC bus voltage and hysteresis current controller is employed to generate signal for switching purpose. The process is based on sensing line currents, filter currents and DC side capacitor voltage. The error signal caused by the filter has been computed firstly. Then this error signal has been compensated using the PID controller. The reference filter currents signal then obtained by subtracts the line current with the compensated signal from the controller. This reference current is feed to the hysteresis current controller and compare with the sensed filter currents to obtain the switching signal for active power filter. Simulation results are obtained with the conventional PID. The results are compared and analyzed. The proposed method offers an efficient control method under the varying load and supply conditions. Based on the simulation and experiment results this project verified the ability of proposed method to compensate harmonics generated by the single phase rectifier battery charger.